2012
DOI: 10.5267/j.msl.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the relative efficiency of Ilam hospitals using data envelopment analysis

Abstract: Measuring the relative efficiency is one of the most important issues among hospitals in today's economy. These days, we hear that cost reduction is a necessity for survival of business owners and one primary to reduce the expenditures is to increase relative efficiency. The proposed study of this paper first uses output oriented data envelopment analysis (DEA) to measure the relative efficiencies of nine hospitals. The proposed model uses four types of employee namely specialists, physicians, technicians and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Data envelopment analysis (DEA) is one of the most popular techniques among both practitioners and scientists (Kuah et al, 2010;Cooper et al, 2011). The method has been applied for measuring technology (Khouja, 1995), measuring the performance of airports (Roghanian & Foroughi, 2010), supplier selection (Levary, 2008;Azar et al, 2011;Nourbakhsh et al, 2013) and heath care (Ghotbuee et al, 2012;Khani et al, 2012). Charnes et al (1978Charnes et al ( , 1985Charnes et al ( , 1990) are believed to be the first who introduced the idea of measuring non-financial units based on various inputs/outputs.…”
Section: Introductionmentioning
confidence: 99%
“…Data envelopment analysis (DEA) is one of the most popular techniques among both practitioners and scientists (Kuah et al, 2010;Cooper et al, 2011). The method has been applied for measuring technology (Khouja, 1995), measuring the performance of airports (Roghanian & Foroughi, 2010), supplier selection (Levary, 2008;Azar et al, 2011;Nourbakhsh et al, 2013) and heath care (Ghotbuee et al, 2012;Khani et al, 2012). Charnes et al (1978Charnes et al ( , 1985Charnes et al ( , 1990) are believed to be the first who introduced the idea of measuring non-financial units based on various inputs/outputs.…”
Section: Introductionmentioning
confidence: 99%
“…Khani et al. (2012) measure the relative efficiency of hospitals using DEA, using a model with four types of employees, namely specialists, physicians, technicians, and other staff as input parameters. The model also uses the number of surgeries, hospitalizations, and radiography as the outputs of the proposed model.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In summary, many studies focus on physical measures of hospital efficiency, financial measures, and quality efficiency measures (Khani et al., 2012; Lee, 2014; Ferreira et al., 2020). However, no study was found to encompass all these variables into hospital efficiency.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Data envelopment analysis (DEA) is one of the most popular methods for measuring non-financial units (Charnes, 1978) and it has been successfully applied for measuring the performance of various technologies (Khouja, 1995), in airport industry (Roghanian & Foroughi, 2010), supplier selection (Levary, 2008;Azar et al, 2011;Nourbakhsh et al, 2013) and heath care (Ghotbuee et al, 2012;Khani et al, 2012). Charnes et al (1978Charnes et al ( , 1985Charnes et al ( , 1990 are named as the first who introduced the idea of comparing non-financial units based on different inputs/outputs.…”
Section: Introductionmentioning
confidence: 99%